RANCANG BANGUN SISTEM SILENT COMMUNICATION MENGGUNAKAN CAHAYA LASER BERBASIS ARDUINO NANO UNTUK MENDUKUNG KOMUNIKASI TAKTIS PADA LINGKUNGAN MILITER - Legowo, Danang; Rimbawa, H.A Danang; Hutapea, Herwin Melyanus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of military communication technology requires communication systems that are secure, difficult to detect, and resistant to Radio Frequency (RF) jamming. One promising alternative is Optical Wireless Communication (OWC) using laser light, which operates in the optical spectrum and is therefore immune to RF interference. This study aims to design and evaluate a laser-based Silent Communication system using an Arduino Nano for military communication applications. An experimental method was employed through the design, implementation, and testing of a prototype consisting of an Arduino Nano, a laser diode as the transmitter, and a light sensor as the receiver. Data transmission was performed using On-Off Keying (OOK) modulation over a Line-of-Sight (LOS) communication link. Experimental results show that the proposed system maintains a transmission rate of 15 bps. The system achieved a 100% Success Rate with a 0% Bit Error Rate (BER) at transmission distances of 5–200 m. At 300 m and 400 m, the Success Rate decreased to 93% and 86%, with BER values of 6.67% and 13.33%, respectively, due to reduced optical signal intensity. In addition, the system showed no significant performance degradation under RF interference because communication was conducted entirely through the optical spectrum. These results demonstrate that the proposed system was successfully implemented and provides Low Probability of Intercept (LPI) and Low Probability of Detection (LPD) characteristics, making it a promising alternative tactical communication solution for modern military operations.